Role of Endoscopy in the Management of Boerhaave Syndrome - Juan Ignacio Tellechea; Jean-Michel Gonzalez; Pablo Miranda-García; Adrian Culetto; Xavier Benoit D'Journo; Pascal Alexandre Thomas; Marc Barthet (Korean Society of Gastrointestinal Endoscopy, 2018)
Boerhaave syndrome (BS) is a spontaneous esophageal perforation which carries high mortality. Surgical treatment is well established, but the development of interventional endoscopy has proposed new therapies. We expose our experience in a Gastrointestinal and Endoscopy Unit. With a retrospective, observational, open-label, single center, consecutive case series. All patients diagnosed with BS who were managed in our center were included. Treated conservatively, endoscopically or surgically, according to their clinical condition and lesion presentation. Fourteen patients were included. Ten were treated with primary surgery. One conservatively. In total, 7/14 patients required an endoscopic treatment. All required metallic stents deployment, 3 cases over-the-scope-clips concomitantly and one case a novel technique an internal drain. 6/7 cases endoscopically treated achieved complete esophageal healing. In conclusion, endoscopy is an useful tool at all stages BS management: difficult diagnosis, primary treatment in selected patients and as salvage when surgery fails. With mortality rates and outcomes comparables to surgery.